Indigenous Fathering and Wellbeing: Kinship and Decolonial Approaches to Health Research - Laura Hall; Tanya Shute; Parveen Nangia; Mikaela Parr; Phyllis Montgomery; Sharolyn Mossey (Diversity of Research in Health Journal, 2020)
In the past decade, Canadian statistics indicate that fathering nurtures family wellbeing which ultimately fosters community growth. The wellbeing of Indigenous men, shaped by determinants of health and culture-based perspectives, is challenged by ongoing settler colonialism. In particular to Indigenous men living with children in their homes, less is known about their strengths as nurturers. For the purpose of this study, based on Indigenist, decolonizing theories, 'father' is not conceived as the head of household. An alternative to the heteropatriarchal model is the kinship orientation of Indigenous fathering and as such, father refers to uncle, grandfather, traditional Clan leader, adoptive parent, and so on. This study's secondary quantitative analysis  compared health and social characteristics of three cohorts of Indigenous adult men who identify as residing with children. Based on an extracted subset of variables from the 2012 Aboriginal Peoples Survey, results showed many significance comparisons among First Nations, Metis and Inuit men. Across health and social domains, multiple and decolonial supports are needed for Indigenous fathering to flourish.